2016
DOI: 10.1080/03043797.2016.1190689
|View full text |Cite
|
Sign up to set email alerts
|

Active Learning session based on Didactical Engineering framework for conceptual change in students’ equilibrium and stability understanding

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Estas innovaciones se han utilizado cuando existen dificultades para la asistencia a las aulas físicas [3], cuando el tiempo requerido para realizar las actividades en el laboratorio supera el asignado, o como forma complementaria a las prácticas presenciales [4]. Un ejemplo son los Laboratorios Remotos (LR) que otorgan la posibilidad de operar a distancia un equipo real con todas las perturbaciones que el entorno pueda tener, lo que permite enriquecer el proceso de aprendizaje y la consolidación de conceptos a través de la observación, interpretación, comparación y análisis de los resultados [5].…”
Section: Marco Teóricounclassified
“…Estas innovaciones se han utilizado cuando existen dificultades para la asistencia a las aulas físicas [3], cuando el tiempo requerido para realizar las actividades en el laboratorio supera el asignado, o como forma complementaria a las prácticas presenciales [4]. Un ejemplo son los Laboratorios Remotos (LR) que otorgan la posibilidad de operar a distancia un equipo real con todas las perturbaciones que el entorno pueda tener, lo que permite enriquecer el proceso de aprendizaje y la consolidación de conceptos a través de la observación, interpretación, comparación y análisis de los resultados [5].…”
Section: Marco Teóricounclassified
“…Research about science teachers' perceptions generally focused on their views about particular educational strategies (Anagün, 2018;Feyzioğlu, 2019), implementation of approaches such as Science, Technology, Engineering, Arts and Mathematics (STEAM), integrated teaching and learner-centred strategies (Du Plessis, 2020;Park et al, 2016;Tudor, 2015) and the teaching of science in general (Qhobela & Moru, 2014). The topic of forces is very important in the physics curriculum because it is part of the curriculum for students who will pursue STEM careers, such as engineering (Canu et al, 2017). However, it has been found that the way it is taught is not helpful in helping students correct their misconceptions such as "continuous force is needed for continuous motion to take place" (Khandagale & Chavan, 2017, p. 202).…”
Section: Research Problemmentioning
confidence: 99%
“…The problems seem easy when the instructor works them at the board; it is not until problems are assigned and students get stuck part way through or fail to complete them that real learning occurs." [48] (p. 188) [40,41,43,47,48,68,82,84,85] Learning theory (n = 8) 1…”
Section: The Argument For Use Example Referencesmentioning
confidence: 99%
“…Dewey (p. 7,1938) argued that "there is an intimate and necessary relation between the processes of actual experience and education"." [53] (p. 116) [39,42,43,47,53,59,61,77] Overall trend (n = 6) 1…”
Section: The Argument For Use Example Referencesmentioning
confidence: 99%